2022-RA-1131-ESGO Human papillomavirus genotype and prognostic factors of vaginal cancer. (20th October 2022) - Lai, Chyong-Huey; Tung, Hsiu-Jung; Wang, You-Chen; Liao, Min-Jie; Jung, Shih-Ming; Yang, Lan-Yan
Abstract : Introduction/Background: The natural history of invasive vaginal cancer has been minimally investigated. We aimed to investigate HPV distribution and prognostic factors in vaginal cancer (VC). Methodology: We retrospectively reviewed medical records of patients with VC who received primary treatment between 1989 and 2020. General polymerase chain reaction (PCR) SPF1/GP6+ followed by revert-blot detection was performed for human papillomavirus (HPV) genotyping. E6 type-specific PCR of the top-5 prevalent types was performed to reconfirm HPV-negative status. P16INK4a immunohistochemistry staining was performed. Univariate and multivariate analyses were performed to identify predictors of clinical outcomes. Results: A total of 73 vaginal carcinoma patients eligible for analysis. Medial follow-up time was 88.6 months (range 0.56–239.5 months). 66 patients (90.4%) were diagnosed as squamous cell carcinoma (SCC) and 7 (9.6%) as non-SCC. HPV DNA sequences were detected in 88.7% of SCC specimens, and 83.3% of non-SCC VC ( P = 0.543). The leading types were HPV16 (51.7%), HPV52 (13.3%) and HPV58 (11.7%). HPV-positivity was associated with better 5-year cancer-specific survival (CSS) (70.8% vs 35.7%, P = 0.005). Because there was strong correlation between p16-positivity and HPV-positivity ( P <0.001), they were alternatively entered in multivariate analysis. In both models, pelvic lymph node (PLN) metastasis (HR 4.72, 95%confidence interval [CI] 1.505–14.804, P = 0.008 or 6.35, 95%CI 1.871–21.564, P = 0.003) was a significant adverse predictor of CSS, while p16 (HR 0.049, 95%CI 0.01- 0.229, P <0.001) or HPV-positivity (HR 0.129, 95%CI 0.036–0.466, P = 0.002) was related to better prognosis. International Federation of Gynaecology and Obstetrics stage (III/IV vs I/II) was significant in univariate analysis, but was not significant in either model. Conclusion: PLN metastasis was a significant adverse predictor, while p16-positivity or HPV-positivity (alternatively) was a significant factor of better prognosis.